2008
DOI: 10.1080/07373930802307167
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Effect of Chemical, Microwave, and Pulsed Electric Pretreatments on Convective Drying and Quality of Raisins

Abstract: In order to discourage the use of chemicals in raisin processing, the effect of microwave and pulsed electric field (PEF) pretreatments on the drying rate and other quality parameters like color, total soluble solids, bulk density, appearance, and market quality were compared with that of chemically pretreated raisins dried at 65 C. The untreated and pretreated samples had a statistically significant difference in drying rate (P < 0.05). The drying rate of chemically pretreated raisins was the highest when com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 13 publications
5
46
0
Order By: Relevance
“…The optimization results for each of the 3 pulse parameters with respect to the 3 measured quality indicators were as follows: The optimal ascorbic acid oxidase activity Y was U g For this activity X V cm X s andX (11) In the samples without PEF treatment, the Vc content was 87.8 ± 2.87 mg•kg -1 , the ascorbic acid oxidase activity was 0.1240 ± 0.0048 U•g -1 , the drying rate was 0.72 ± 0.02 h -1 . These results of samples with PEF treatment demonstrate that drying rate and Vc content were optimized with a low pulse intensity, short treatment time, and appropriate pulse number.…”
Section: Optimization Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The optimization results for each of the 3 pulse parameters with respect to the 3 measured quality indicators were as follows: The optimal ascorbic acid oxidase activity Y was U g For this activity X V cm X s andX (11) In the samples without PEF treatment, the Vc content was 87.8 ± 2.87 mg•kg -1 , the ascorbic acid oxidase activity was 0.1240 ± 0.0048 U•g -1 , the drying rate was 0.72 ± 0.02 h -1 . These results of samples with PEF treatment demonstrate that drying rate and Vc content were optimized with a low pulse intensity, short treatment time, and appropriate pulse number.…”
Section: Optimization Results and Analysismentioning
confidence: 99%
“…Although PEF and microwave pretreatments can shorten drying times by only about 20%, the quality of the products processed using these pretreatment methods is better than that of chemically pretreated samples or untreated samples. [11] In addition, a study on carrot drying showed that the drying time of PEF-pretreated carrots was 20% less than that of untreated samples. [7] Another recent study reported that PEF pretreatment of red pepper reduced drying time by 34.7%.…”
Section: Introductionmentioning
confidence: 98%
“…[148] Similar results were found when MW and pulsedelectric field (PEF) pre-treatments were studied for their application to raisin production, where it was found that both had an effect on drying rate. [149] PEF has also been applied in order to disrupt the cellular structure of food products prior to air drying. Again, the applicability is in question, as in the case of potato slices, the drying rate was found to be unaffected during subsequent microwave-convective drying.…”
Section: Operationsmentioning
confidence: 99%
“…Samples dried by the MIRD (25 min)-FD combination showed the lowest rehydration ratio and the highest apparent density (p < 0.05). The pore size distribution in the internal structure of dried products greatly affects both the apparent density and rehydration (Karathanos, 1993;Dev et al, 2008). In the case of samples which were subjected to MIRD before FD, it is difficult for water within the mushroom matrix to diffuse out because the surface of mushroom forms a crust.…”
Section: Rrmentioning
confidence: 99%